Overlapping phenotypes between SHORT and Noonan syndromes in patients with PTPN11 pathogenic variants. Issue 1 (22nd April 2020) - Ranza, Emmanuelle; Guimier, Anne; Verloes, Alain; Capri, Yline; Marques, Charles; Auclair, Martine; Mathieu‐Dramard, Michèle; Morin, Gilles; Thevenon, Julien; Faivre, Laurence; Thauvin‐Robinet, Christel; Innes, A. Micheil; et al.
Abstract: Overlapping syndromes such as Noonan, Cardio‐Facio‐Cutaneous, Noonan syndrome (NS) with multiple lentigines and Costello syndromes are genetically heterogeneous conditions sharing a dysregulation of the RAS/mitogen‐activated protein kinase (MAPK) pathway and are known collectively as the RASopathies. PTPN11 was the first disease‐causing gene identified in NS and remains the more prevalent. We report seven patients from three families presenting heterozygous missense variants in PTPN11 probably responsible for a disease phenotype distinct from the classical Noonan syndrome. The clinical presentation and common features of these seven cases overlap with the SHORT syndrome. The latter is the consequence of PI3K/AKT signaling deregulation with the predominant disease‐causing gene being PIK3R1 . Our data suggest that the phenotypic spectrum associated with pathogenic variants of PTPN11 could be wider than previously described, and this could be due to the dual activity of SHP2 (ie, PTPN11 gene product) on the RAS/MAPK and PI3K/AKT signaling. Abstract :